Constraints and prospects of local newspapers : a study based on 9 coastal districts of Bangladesh - Siddiqui, Arshad; Husen, Javed; Mass-Line Media Center (Dhaka, Bangladesh) (Dhaka : Mass-line Media Centre, 2002)
With reference to Bangladesh.
Includes bibliographical references (p. 135-137).
Keywords: Press and politics -- Bangladesh; Newspapers -- Political aspects -- Bangladesh; Journalism -- Objectivity -- Bangladesh; Newspapers -- Local editions